Efficient thermally activated delayed fluorescence of functional phenylpyridinato boron complexes and high performance organic light-emitting diodes. Issue 6 (25th January 2017) - Shiu, Yi-Jiun; Chen, Yi-Ting; Lee, Wei-Kai; Wu, Chung-Chih; Lin, Tzu-Chieh; Liu, Shih-Hung; Chou, Pi-Tai; Lu, Chin-Wei; Cheng, I-Chen; Lien, Yi-Jyun; Chi, Yun
Abstract : A new series of functional phenylpyridinato boron complexes possessing thermally activated delayed fluorescence (TADF) has been strategically designed and synthesized. Abstract : A new series of functional phenylpyridinato boron complexes possessing thermally activated delayed fluorescence (TADF) has been strategically designed and synthesized. These boron complexes utilize phenylpyridine as the electron acceptor (A) that links to carbazole or triphenyl amine as the electron donor (D) via a core boron atom, forming four-coordinate neutral boron complexes. The selection of boron to spatially separate the donor and acceptor takes advantage of facile functionalization. The TADF properties of the resulting D–A functional materials in various solvents have been investigated via their emission spectra and associated relaxation dynamics. The results show that the operation of TADF is strongly solvent polarity dependent in fluid states, and several underlying mechanisms are discussed. OLEDs fabricated byfppyBTPA anddfppyBTPA show EL efficiencies of up to (20.2%, 63.9 cd A −1, 66.9 lm W −1 ) and (26.6%, 88.2 cd A −1, 81.5 lm W −1 ), respectively, in which a nearly 27% EQE for thedfppyBTPA device is among the most efficient TADF OLEDs so far.